Simulation of Interaction Between Groundwater and Surface Water in Safwan-Zubair Area, South of Iraq - Mnati, Maher Ashour; Al-Aboodi, Ali H.; Hassan, Ayman A. (Basrah Journal for Engineering Sciences, 2023)
Groundwater in arid and semi-arid regions, such as the studied area (Safwan Al-Zubair area, south of Iraq), is of specific meaning as a major source for domestic use and irrigation demand. There is a need to better understand the interactions between groundwater and surface water (Shatt Al-Basrah Canal). These interactions can negatively affect the quality of groundwater in this area, especially that the water of Shatt Al- Basrah Canal contains highly concentrated pollutants. The aim of the study is to investigate the temporal disparity of river-aquifer interactions and count the amount of river interchange among canal and aquifer. In this research, a new concept of paradigm will be advanced utilizing RIVER package of Groundwater River Paradigm (MODFLOW) for the simulation of river-aquifer interaction operations. Six monitoring wells are chosen to evaluate the preliminary and historical groundwater hydraulic heads for six months and then use all collected data in Modflow to execute the simulation of numerical modeling to assessment the interaction between surface water and groundwater. The amount of seepage out from the canal towards the aquifer was (64.99 m 3 /day) in wet season (winter season), as a result of the high levels of the surface water compared to the hydraulic heads of groundwater. The amount of seepage in dry season towards the aquifer is equal to (336.8 m 3 /day).